2011
DOI: 10.1158/1940-6207.prev-11-a39
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A39: EGCG, a green tea polyphenol, can reverse methylation related silencing of genes in human colon carcinomas

Abstract: Silencing of regulatory genes through hypermethylation of CpG islands is an important mechanism in tumorigenesis. In colon cancer, RXRα, an important dimerization partner with other nuclear transcription factors, is silenced through this mechanism. Previous studies from our laboratory have shown that ApcMin/+ mice treated with the carcinogen azoxymethane (AOM) will develop colonic tumors but when treated with green tea a reduction in tumor numbers was found. We found that colon tumors had lower expression of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that CLS lesions occur in white adipose tissue of the breast in obese women and in the mammary gland of experimental models of obesity (Morris et al, 2011; Subbaramaiah et al, 2011). Importantly, in mouse models of obesity, CLS occur in association with activation of NF-κB and elevated levels of inflammatory mediators including TNF-α, IL-1β, and COX-2 (Subbaramaiah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that CLS lesions occur in white adipose tissue of the breast in obese women and in the mammary gland of experimental models of obesity (Morris et al, 2011; Subbaramaiah et al, 2011). Importantly, in mouse models of obesity, CLS occur in association with activation of NF-κB and elevated levels of inflammatory mediators including TNF-α, IL-1β, and COX-2 (Subbaramaiah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%